The influence of awe and augmented reality (AR) for driving tourists' loyalty towards religious destinations - Nascimento, J. (2023)
Religious tourism is one of the most important touristic segments globally. Yet, thecognitive and emotional processes shaping destination loyalty in this context, and theimpacts of Augmented Reality (AR) technology were not fully investigated. This studytakes a unique approach to examine how awe influences recommendation and revisitingintentions through the mediation of rational (e.g., authenticity) and affective (e.g.,emotional) mechanisms. Furthermore, our research unveils the role of AR for reinforcing the future intentions of tourists towards a religious site.